ICP 2005 CONSTRUCTION PRICES: ARE THEY UNDERESTIMATED IN DEVELOPING COUNTRIES? (2015)
Construction prices are lower in developing countries in ICP 2005, which has raised these countries’ capital/output ratio in Penn World Tables 7 and 8 and affected growth analyses. We estimate the Colombia/U.S. price ratio for office and apartment buildings in 2005 as a test of the validity of the ICP 2005 methodology for estimating these prices. Our estimate of the Colombia/U.S. price ratio is almost twice the ICP 2005 estimate. We confirm the validity of our results by estimating the cost of constructing office and apartment buildings using 2005 prices for construction materials, equipment, and labor in both countries.